2023
DOI: 10.3390/pharmaceutics15051360
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Crosstalk between Lipids and NADPH Oxidases in Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is a serious complication of diabetes mellitus and a leading cause of end-stage renal disease. Abnormal lipid metabolism and intrarenal accumulation of lipids have been shown to be strongly correlated with the development and progression of diabetic kidney disease (DKD). Cholesterol, phospholipids, triglycerides, fatty acids, and sphingolipids are among the lipids that are altered in DKD, and their renal accumulation has been linked to the pathogenesis of the disease. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 186 publications
0
5
0
Order By: Relevance
“…And the median of 12(S)-HETE in T2DM with DKD group was 97.07 (10.57, 737.40), while the median of 12(S)-HETE in T2DM group was 53.06 (11.26, 185.30). Dysregulated lipid metabolism and the intarenal deposition of lipids have been demonstrated to be closely linked with the development and progression of DKD [22]. Among which, cholesterol, phospholipids, TC, fatty acids, and sphingolipids are lipid types that undergo changes in DKD, and their accumulation in the kidneys has been associated with the development of the disease [22].…”
Section: Serum 12(s)-hete Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…And the median of 12(S)-HETE in T2DM with DKD group was 97.07 (10.57, 737.40), while the median of 12(S)-HETE in T2DM group was 53.06 (11.26, 185.30). Dysregulated lipid metabolism and the intarenal deposition of lipids have been demonstrated to be closely linked with the development and progression of DKD [22]. Among which, cholesterol, phospholipids, TC, fatty acids, and sphingolipids are lipid types that undergo changes in DKD, and their accumulation in the kidneys has been associated with the development of the disease [22].…”
Section: Serum 12(s)-hete Measurementmentioning
confidence: 99%
“…Dysregulated lipid metabolism and the intarenal deposition of lipids have been demonstrated to be closely linked with the development and progression of DKD [22]. Among which, cholesterol, phospholipids, TC, fatty acids, and sphingolipids are lipid types that undergo changes in DKD, and their accumulation in the kidneys has been associated with the development of the disease [22]. The clinical data showed that DKD patients had a higher LDL-c/HDL-c and TC/HDL-c levels (Fig.…”
Section: Serum 12(s)-hete Measurementmentioning
confidence: 99%
“…Renal TG accumulation in patients with DKD is associated with the dysregulated expression of genes involved in lipid metabolism ( 97 ). Renal biopsies from patients with DKD showed decreased expression of genes encoding PPAR-α and PPARδ and their downstream acyl-coenzyme A oxidase and carnitine palmitoyl transferase (CPT1) involved in the fatty acid β-oxidation pathway, and SREBP, a transcription factor regulating FA synthesis, induced fluorescent antibody serum neutralization (FASN) and acetyl Coenzyme A(CoA) carboxylation.…”
Section: Mechanisms Of Lipid Metabolic Changes In Dkdmentioning
confidence: 99%
“…These molecules cause direct tissue damage and induce the formation of ROS, contributing to OS [10]. NADPH oxidase, an enzyme complex producing superoxide radicals, sees elevated activity in DM, leading to increased ROS synthesis, especially impactful in vascular tissues due to its role in endothelial dysfunction [11]. The polyol pathway, an additional glucose metabolism mechanism, results in sorbitol and fructose accumulation in DM, exacerbating OS by utilizing NADPH, necessary for antioxidant production [12].…”
Section: Mechanisms Of Os Generationmentioning
confidence: 99%